The playful life of a community of candomblé in the Cubango: a study on the category "joke" - Gonçalves, Maria Alice Rezende (Cadernos CERU, 1999)
This article is about a research that investiges the spare time activities of the members of a candomblé community in Niteroi/RJ highlighting the period dedicated to the ludicrous activities which take place in this "terreiro". First, it has been found out that the notation of time which arises in such a context is different from the one dominanting in our society and has been described as "task orientation" is common appear to show least demarcation between work and life. Third, "brincadeira" is used category for this group to classify the entarteinement activities. Finally, this research classifies the parties as extraordinary events wich distinguish the passage of the time serapating them in two groups: the "houses parties" and the "street paty".